STRATEGI GURU PADA PENINGKATAN KEDISIPLINAN SISWA DI SMPN 5 MATARAM - Komang Devi Anggraini; Ida Bagus Rama Juni Artana; I Komang Ananda Widya Pratama; I Wayan Rudiarta (Jawa Dwipa, 2025)
The discipline behavior of students of SMPN 5 Mataram in the learning process is still not good enough, so a strategy is needed by teachers to improve student discipline. This study aims to determine the level of student discipline, examine the strategies used by teachers to improve student discipline, and analyze the obstacles faced by teachers in their efforts to improve student discipline. This study uses a qualitative descriptive research method, including non-participant observation, semi-structured interviews, and documentation for data collection. The data obtained were then analyzed through three stages: data reduction, data presentation, and formulation of conclusions. Based on the results of the research conducted, three findings were obtained, namely 1) Low student discipline behavior is reflected in the learning process such as lack of student attention to learning, delays during learning, and disobedience to established regulations; 2) The teacher's strategy used as an effort to improve student discipline is to use a cooperative strategy where students are formed into small groups in learning to jointly solve a problem given by the teacher. This aims to create a sense of responsibility and awareness as the forerunner to the formation of student discipline; 3) Challenges and obstacles for teachers in efforts to improve student discipline, namely: Lack of student awareness of the need for discipline, lack of support and guidance from parents and family, and students' social interactions in the community.